Characterization of Mg-independent and Mg-dependent Ecto-ATPase activities in luminal a breast cancer MCF-7 cells - Lacerda-Abreu, Marco Antonio; Silva, Enderson; Mendonça, Bruna dos Santos; de Moraes, Gabriela Nestal; Meyer-Fernandes, José Roberto (Biochemical and biophysical research communications, 2025)
Breast cancer remains the most prevalent malignancy among women, characterized by molecular heterogeneity and complex tumor microenvironment interactions. Purinergic signaling, particularly through extracellular adenosine triphosphate (ATP) hydrolysis, plays a significant role in regulating cancer progression. Ectonucleotidases and ectophosphatases modulate ATP and inorganic phosphate (Pi) metabolism, thereby influencing tumor-associated processes such as migration and adhesion. In this study, we biochemically characterized ecto-ATPase activity in luminal breast cancer cells (MCF-7) and compared it to non-tumorigenic breast epithelial cells (MCF10-A). We identified distinct Mg2+-dependent and independent ecto-ATPase activities, with MCF-7 cells exhibiting a significant Mg2+-dependent increase in ATP hydrolysis. Kinetic analyses revealed that Mg2+-independent activity presents higher substrate affinity, whereas the Mg2+-dependent enzyme displays greater catalytic capacity. Substrate specificity assays demonstrated preferential hydrolysis of ATP and ADP, highlighting the potential role of ecto-ATPase in extracellular nucleotide homeostasis. Pharmacological inhibition with ARL67156 reduced Mg2+-dependent ecto-ATPase activity, leading to a significant decrease in cell migration and adhesion, indicating a functional role in breast cancer progression. These findings underscore the relevance of ecto-ATPase in luminal breast cancer and its potential as a therapeutic target. Future investigations should explore its interplay with purinergic signaling and oncogenic pathways to develop novel strategies for targeted breast cancer treatment. •Magnesium-dependent and magnesium-independent ecto-ATPase activities were identified in luminal A MCF-7 breast cancer cells.•Higher ecto-ATPase activity is found in breast cancer compared to non-tumoral breast cells.•Ecto-ATPase activity is associated with cell adhesion and migration in MCF-7 cells.